SIKAP KONSUMTIF SEBAGAI BUDAYA POPULER DAN KOMUNIKASI ANTAR BUDAYA DALAM PLATFORM DIGITAL - Aini, Fatimatuzahrotul; Rahmah, Atikah; Aeni, Nur (Ilmu Komunikasi, FISIP Universitas Pasundan, 2026)
The rapid development of digital platforms has transformed patterns of consumption in modern society, particularly among younger generations. Digital platforms function not only as spaces for information exchange, but also as media for the dissemination of popular culture and intercultural communication that shape consumerist attitudes. This study aims to analyze consumerism as a form of popular culture and as an intercultural communication practice on digital platforms in Indonesia. This research employs a qualitative descriptive approach using content analysis and non-participant digital observation of social media content, promotional materials, and visual narratives circulating on platforms such as Instagram, TikTok, and e-commerce sites. The findings indicate that digital platforms play a significant role in constructing symbolic consumption, in which products are no longer consumed solely based on their functional value, but also as representations of identity, social status, and lifestyle. Popular culture, reinforced by the role of influencers, social media algorithms, and global cultural flows, encourages consumerist behavior, impulse buying, and the normalization of hedonistic lifestyles. Intercultural communication processes further facilitate the dissemination of global values that negotiate with local cultures, thereby shaping dynamic consumption patterns. This study concludes that consumerist attitudes in digital spaces constitute a socio-cultural phenomenon constructed through media representations, intercultural interactions, and the dynamics of digital capitalism. Therefore, enhancing media literacy and critical awareness is essential to promote more rational and responsible consumption practices.